1992
DOI: 10.1111/j.1751-1097.1992.tb09602.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes of Cytosolic Loops of Bovine Rhodopsin During the Transition to Metarhodopsin‐ii: An Investigation by Fourier Transform Infrared Difference Spectroscopy*

Abstract: In order to assign the structural changes of the protein, observed in the Fourier transform infrared (FT-IR) difference spectra of the rhodopsin-metarhodopsin-II transition, to specific regions of the protein, rhodopsin was treated by proteases. Nonilluminated and bleached rhodopsin was treated with protease K and papain. Rhodopsin digested in the bleached state was subsequently regenerated with 11-cis-retinal. From these modified samples the rhodopsin-metarhodopsin-II FT-IR difference spectra were measured. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 19 publications
(11 reference statements)
2
13
0
Order By: Relevance
“…Although this picture may be more complex than previously characterized, the acid-base transition of C106 clearly creates energy perturbations that are largely compatible with many previous experimental findings [9][10][11][12][13][14][15]. In the unliganded wildtype B2AR, the TM1 Â 7, TM3 Â 4, TM3 Â 5, TM3 Â 6 and TM6 Â 7 interactions are all strongly positive for the unbound WT (B À A) states of the B2AR (gray bars in Fig.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Although this picture may be more complex than previously characterized, the acid-base transition of C106 clearly creates energy perturbations that are largely compatible with many previous experimental findings [9][10][11][12][13][14][15]. In the unliganded wildtype B2AR, the TM1 Â 7, TM3 Â 4, TM3 Â 5, TM3 Â 6 and TM6 Â 7 interactions are all strongly positive for the unbound WT (B À A) states of the B2AR (gray bars in Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Other investigators have also suggested that the cis-trans isomerization of retinal in rhodopsin causes repositioning followed by a movement of TM3 away from TM6 [9,11,15]. Clearly there are many studies that implicate TM3 and TM6 with the molecular events leading to receptor activation.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Mutations affecting cytoplasmic loops I, II, or III, or transmembrane segments (TMS) I, II, VI, or VII, constitutively activate GPCRs by destabilizing the inactive state or stabilizing the active state (Kjelsberg et al, 1992;Robinson et al, 1992;Parma et al, 1993;Robbins et al;Shenker et al, 1993;Konopka et al, 1996;Scheer et al, 1996). Indeed, conformational changes accompanying GPCR activa-tion occur in cytoplasmic loops, near the cytoplasmic terminus of TMS III or VII and within TMS VI (Ganter et al, 1992;Farahbakhsh et al, 1993;Bukusoglu and Jenness, 1996;Lin and Sakmar, 1996). Furthermore, the distance between TMS III and VI increases when rhodopsin is activated Yang et al, 1996).…”
Section: Introductionmentioning
confidence: 99%